2010
DOI: 10.1016/j.jpcs.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties of Ni2+ and rare-earth codoped Ge–Ga–Sb–S glass

Abstract: The infrared emission properties of rare-earth (i.e., Dy 3+ , Pr 3+ or Sm 3+ ) and nickel-codoped Ge-Ga-Sb-S glasses were investigated by photoluminescence measurements. It was found that the emission intensities of the rare-earth doped glasses were significantly weakened even with very few amount of nickel (i.e., 500 atomic ppm). On the other hand, the nickel doped glasses show larger indices of refraction, which property will be desirable in nonlinear optics. Our results, however, suggest that to obtain rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…We chose GGSS glass as a matrix material for it has been characterized as a very good optical material due to its good chemical stability, good thermal stability against crystallization, and a large rare-earth solubility that is beneficial for making fiber lasers and amplifiers. 7 We have found that the diffusion process can be well fitted by the thin-film or thick-film model depending on the diffusion temperature. Also, the surface refractive index changes significantly after the diffusion.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…We chose GGSS glass as a matrix material for it has been characterized as a very good optical material due to its good chemical stability, good thermal stability against crystallization, and a large rare-earth solubility that is beneficial for making fiber lasers and amplifiers. 7 We have found that the diffusion process can be well fitted by the thin-film or thick-film model depending on the diffusion temperature. Also, the surface refractive index changes significantly after the diffusion.…”
Section: Introductionmentioning
confidence: 85%
“…In this article, we studied the solid‐state EFA diffusion of silver ions into Ge–Ga–Sb–S (GGSS) glasses by secondary ion mass spectrometer (SIMS). We chose GGSS glass as a matrix material for it has been characterized as a very good optical material due to its good chemical stability, good thermal stability against crystallization, and a large rare‐earth solubility that is beneficial for making fiber lasers and amplifiers 7 . We have found that the diffusion process can be well fitted by the thin‐film or thick‐film model depending on the diffusion temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] In addition, the detrimental ET can also lead to severe degradation of PL performance, for example, the baneful effect of Ni 2+ impurity on the quantum yield of rare-earth ions (REs) doped laser glasses. 12 To realize high quantum yield, REs are usually doped in fluoride crystals characterized by low phonon energies (~400 cm À1 ), whereas transition metals (TMs) are doped in oxide crystals with appropriate coordination environments and crystal field strengths. 13,14 Dual-phase glass-ceramics (GCs) containing 2 different NCs (NCs) orderly precipitated from the glassy matrix have recently attracted great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, some researchers have added a relatively high Ga content, for instance: 5 at. % Ga in RE‐doped Ge–Sb–S(Se) glasses, 10 at. % Ga in RE‐doped Ge–S glasses, and 11.8 at.…”
Section: Introductionmentioning
confidence: 99%